2023
DOI: 10.1021/acsami.3c02528
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Platelet-Rich Fibrin Exudate-Loaded Carboxymethyl Chitosan/GelMA Hydrogel for Efficient Bone Defect Repair

Abstract: Platelet-rich fibrin (PRF) is an autologous growth factor carrier that promotes bone tissue regeneration, but its effectiveness is restrained by poor storage capabilities, uncontrollable concentration of growth factors, unstable shape, etc. Herein, we developed a photocrosslinkable composite hydrogel by incorporating lyophilized PRF exudate (LPRFe) into the carboxymethyl chitosan methacryloyl (CMCSMA)/gelatin methacryloyl (GelMA) hydrogel to effectively solve the dilemma of PRF. The hydrogel possessed suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…The unaltered physical characteristics of the hydrogel after its composite formation suggest that it can reliably function in the physiological environment of bone repair. This stability is crucial for ensuring the hydrogel's effectiveness in facilitating osteointegration and promoting tissue regeneration [ 33 , 34 ]. The ability of the hydrogel to maintain its integrity while in close contact with the scaffold underlines its potential as a viable medium for supporting bone healing and regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The unaltered physical characteristics of the hydrogel after its composite formation suggest that it can reliably function in the physiological environment of bone repair. This stability is crucial for ensuring the hydrogel's effectiveness in facilitating osteointegration and promoting tissue regeneration [ 33 , 34 ]. The ability of the hydrogel to maintain its integrity while in close contact with the scaffold underlines its potential as a viable medium for supporting bone healing and regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels acted as a scaffold for chemical drugs, proteins, and stem cells and could effectively promote wound healing of the spinal cord. However, genetic materials delivered by hydrogel scaffolds are ideal for more demanding conditions, offering protection of the genetic material from enzymes, the capability to retain drugs at a high level, and injectable biocompatibility with easy sol–gel phase transition at the lesion location. In order to fit these demanding conditions, there are various sensitive scaffolds with phase transition triggered by temperature, pH, and photoexposure. GelMA hydrogels have great biocompatibility and phase transition properties, which are widely applied in regenerative medicine. GelMA is mostly used as a hydrogel scaffold to load with various stem cells in therapy . However, we combined GelMA with gene therapy for SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies further reported that hydrogel showed excellent biocompatible and biodegradable characteristics, and its good capacity, when loaded with LPRFe, to expedite the bone healing procedure efficiently. In summary, the prepared hydrogel holds promise as a therapeutic approach for addressing defects in bone [114].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…(iv) Illustration of CMCS/GelMA hydrogel incorporated with LPRFe for repairing bone defect. Reprinted with permission from[114]. Copyright (2023) American Chemical Society.…”
mentioning
confidence: 99%